1991
DOI: 10.1017/s0022112091001313
|View full text |Cite
|
Sign up to set email alerts
|

Surface wave and thermocapillary instabilities in a liquid film flow

Abstract: A liquid film flowing down an inclined heated plane subject to surface wave and thermocapillary instabilities is studied. Three mechanisms exist by which energy can be transferred to the disturbance. Two of these mechanisms are associated with the thermocapillary forces and one with the shear stress of the basic flow at the deformed free surface. Depending on which mechanism is dominant, the instability can assume the form of either long transverse waves or short longitudinal rolls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
90
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(105 citation statements)
references
References 21 publications
14
90
1
Order By: Relevance
“…2. The solid line shows the linear stability result found from the pure thermocapillary problem [9] or equivalently from our model by suppressing the streamwise dependence:…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…2. The solid line shows the linear stability result found from the pure thermocapillary problem [9] or equivalently from our model by suppressing the streamwise dependence:…”
mentioning
confidence: 81%
“…Three-dimensional hydrodynamic waves have been investigated experimentally by various authors [3][4][5] who have provided a clear picture of the phenomenology and intricate dynamics of interacting 3D waves in isothermal film flows. When the falling film is uniformly heated from the wall, as encountered in thin-film evaporators and cooling of electronics, its dynamics is influenced, in addition to inertia and surface tension, by the variation of surface tension with temperature, namely the long-wave thermocapillary (Marangoni) effect [6][7][8], which possibly leads to rivulet-(a) E-mail: bscheid@ulb.ac.be like structures aligned with the flow as predicted by linear stability analysis [9]. Joo et al [10] modeled the nonlinear stage of such rivulet structures by incorporating the Marangoni effect into the Benney equation (MBE).…”
mentioning
confidence: 99%
“…We restrain the present study to the two-dimensional case for at least the three follow-ing reasons: (i) we want to benefit from the dynamical-system theory (see §2.1.2) that cannot be applied with a third coordinate; (ii) the linear growth rate of transverse waves was found by Goussis & Kelly (1991) to be always larger than that of longitudinal rolls as far as the long-wave modes are concerned. Note that this result extends the one obtained for the pure hydrodynamic mode by Yih (1955) who extended the Squire's approach to free surface flows (Huerre & Rossi 1998); (iii) as a consequence of the previous point and as shown experimentally, it always exists a transition zone of purely two-dimensional flow when the film is periodically forced at the inlet (Liu et al 1995).…”
Section: Frame and Objectives Of This Workmentioning
confidence: 99%
“…The linear stability analysis by Ludviksson & Lightfoot [11] considered the free surface as adiabatic thus demonstrating the crucial role of the imposed streamwise temperature gradient in the instability mechanism. On the contrary, Goussis & Kelly [18] analyzed the case of an inclined plate maintained at constant temperature, and showed that only a non-adiabatic free surface in this case can lead to the long-wave thermocapillary instability and concomitant streamwise roll cells, i.e. rivulets, A sketch of rivulet structures is given in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism in this case is the same that the one described by Smith [19] to explain the dewetting of a thin film on a heated horizontal substrate: a spontaneous modulation of the freesurface elevation generates a temperature gradient at the interface and once flow starts, it is again maintained by the externally imposed temperature gradient (directed across the film). Goussis & Kelly [18] have therefore shown that a gravity-driven flow due to the plate inclination breaks the isotropy of the long-wave thermocapillary instability and aligns the structure with the flow. The wavelength of the instability, however, remains unchanged, at least in the linear regime.…”
Section: Introductionmentioning
confidence: 99%